A4 THE CIRCADIAN TIMING OF INFLAMMATORY BOWEL DISEASE. (4th March 2021) - Taleb, Z; Stokes, K; Wang, H; Collins, S M; Khan, W I; Karpowicz, P
Abstract: Background: The circadian clock is a highly conserved molecular pacemaker found in nearly every cell of the body. It consists of the genes BMAL1 and CLOCK that positively regulate CRY and PER, their negative regulators, resulting in a transcription/translation feedback loop that has a 24 hour cycle. This core clock mechanism drives the rhythmic expression of over 40% of the genome in a tissue-specific manner and therefore imposes 24 hour rhythms on many physiological processes. Shift work, which causes disruptions to the natural 24 hour physiological rhythms, has been shown to lead to an increased incidence of inflammatory bowel disease (IBD). Aims: This study aims to characterize daily rhythms in inflammation and regeneration of the colon upon induction of acute colitis. We also aim to investigate the intestinal epithelial-specific effects of circadian clock disruption on overall disease progression. We hypothesize that the absence of a functional circadian clock eliminates proliferation rhythms of intestinal epithelial cells and disrupts the rhythms of inflammatory cytokines, thereby increasing the pathogenesis of IBD. Methods: We tested the role of the clock in IBD using BMAL1 +/+ (wild type) and BMAL1 -/ - (null mutant) mice. We also investigated the effects of the circadian clock specific to intestinal epithelial tissue using Vil +/+ ;BMAL1 flox/flox (control) and Vil Cre/+ ;BMAL1 flox/flox (conditional intestinal epithelial mutant) mice. Dextran Sulfate Sodium (DSS) was applied to induce acute colitis. Results: We observed significantly decreased survival of BMAL1 circadian clock mutant mice when given colitis. A histology analysis indicates increased lesioning and overall inflammation in BMAL1 -/ - colon tissue. Disease activity and cytokine analyses reveal time-dependent severity in inflammatory response that is worse in BMAL1 -/ - mice. To test the circadian rhythms in intestinal regeneration of mice with IBD, we performed a 24 hour analysis comparing epithelial cell proliferation and cell death in colon tissue. We observed rhythmic expression of phosphor-histone H3 (a mitosis marker) in wild type mice which is eliminated in the BMAL1 -/ - lacking a circadian clock. Cell death which was measured by caspase 3 did not exhibit any differences between genotypes. Based on these results, we conclude that the loss of clock function leads to impaired regeneration during IBD, in part due to decreased and arrhythmic cell proliferation. Preliminary results in our Vil Cre/+ ;BMAL1 flox/flox conditional intestinal epithelial mutant mice indicate that some of these effects may be epithelial-specific. Conclusions: Our results support a critical role of the circadian clock in inflammatory bowel disease development. These data highlight that the circadian clock affects the regenerative abilities of intestinal epithelial cells. Funding Agencies: CIHRChron's and Colitis Canada, Ontario, University of Windsor